trans-Activation of the human T-cell leukemia virus long terminal repeat correlates with expression of the x-lor protein. - Sodroski, J G (1985)
Cell lines established directly from adult T-cell leukemia-lymphoma patients or immortalized by human T-cell leukemia virus type I (HTLV-I) in vitro that do not produce complete HTLV virions were characterized both for the content of viral proteins and for the presence of trans-acting factors activating gene expression under the control of the HTLV long terminal repeat. The expression of the 42-kilodalton HTLV x-lor product correlated with trans-activation of the long terminal repeat. The implications of this study for understanding the role of the HTLV x-lor product in the initiation and maintenance of T-lymphocyte transformation are discussed.